CHARLES DICKENS AS A REPRESENTATIVE OF THE CRITICAL REALISM (Modern education and development, 2025)
This article analyzes the role of Charles Dickens, a prominent figure in English literature, as a representative of critical realism and examines the key themes in his works. Writing in the critical realist style, Dickens sharply critiques the social, political, and economic issues of his time, highlighting the complex relationships between social structures and human lives. His novels, particularly “Oliver Twist”, “David Copperfield”, “A Tale of Two Cities”, “Great Expectations”, “Hard times” and “Little Dorrit” are considered some of the most important examples of realism in literature. This paper explores Dickens' contribution to the genre of critical realism and the way he portrayed social criticism in his works.Ushbu maqolada ingliz adabiyoti tarixidagi muhim shaxs bo‘lgan Charlz Dikkensning tanqidiy realizmdagi o‘rni va uning asarlaridagi asosiy mavzular tahlil qilinadi. Tanqidiy realizm uslubida asarlar yozgan Dikkens, ularda jamiyatning ijtimoiy-siyosiy va iqtisodiy muammolarini o‘tkir tanqid qiladi . Asosan asarlarida ijtimoiy tuzilma va inson hayoti bilan bog‘liq murakkab munosabatlarini ko‘rsatadi. Dikkensning romanlari, ayniqsa "Oliver Twist", "David Copperfield", "A Tale of Two Cities", “Great expectation”, “ Hard times “ , “ Little Dorrit” adabiyotda realizmning eng muhim namunalaridan hisoblanadi.В этой статье анализируется роль Чарльза Диккенса, выдающегося деятеля английской литературы, как представителя критического реализма, а также рассматриваются ключевые темы его произведений. Пишущий в стиле критического реализма, Диккенс остро критикует социальные, политические и экономические проблемы своего времени, подчеркивая сложные отношения между социальными структурами и человеческими жизнями. Его романы, такие как Оливер Твист, Дэвид Копперфилд, История двух городов, Большие ожидания, Трудные времена и Маленькая Доррит, считаются одними из самых важных примеров реализма в литературе. В данной статье рассматривается вклад Диккенса в жанр критического реализма и то, как он изображал социальную критику в своих произведениях.